Navigating power dynamics: Guanxi-capitalism and market Access for MNCs in China - Muhammad Aditya Purnomo (Priviet Social Sciences Journal, 2026)
This research emphasizes the intersection between China’s Guanxi principle and capitalism in shaping market access for Multinational corporations (MNC) in the country. The analysis draws upon the theories of state capitalism and transnational capitalism to examine how the guanxi principle functions as both an informal institution and a strategic business tool that serves as a mediator of the power dynamics between the state and private firms. According to this research’s qualitative analysis of secondary sources and case studies, the results indicate that guanxi-capitalism serves as a hybrid mechanism that combines a traditional social networking mechanism among its people with modern economic practices, in which the purpose is to emphasize trust-building, minimize transaction costs, and streamline the MNCs to navigate within the institutional voids. This paper argues that guanxi-capitalism not only enhances formal legal frameworks but also serves as a balancer between state control and private control of the market. Unfortunately, there are numerous Western criticisms regarding the high possibility of corruption and lack of transparency, which are regarded as ethical dilemmas within guanxi capitalism, which occurred in a past MNC operational within China. This study concludes that guanxi-capitalism serves as an example of a blended model of capitalism that combines social norms, state intervention within the market, and global economic participation, which simultaneously redefines traditional Western market governance.